Identification of the trends associated with the SPI and SPEI indices across Ankara, Turkey - Danandeh Mehr, Ali; Vaheddoost, Babak (Springer Wien, 2020)
This study investigates the main characteristics (duration, severity, and trend) of meteorological drought events over Ankara Province, Turkey. We used 46 years of observed monthly precipitation and temperature series from six meteorological stations distributed across the study area to derive the well-known meteorological drought indices; the standardized precipitation index (SPI) and standardized precipitation evapotranspiration index (SPEI) both in 3-, 6-, and 12-month timescales. A comparative analysis between the indices, associated drought events, and potential trends at each station are presented. To explore the drought trends in each station, the well-documented Spearman rank-order correlation coefficient, innovative Sen's method, and innovative trend analysis are applied. The results showed that the province faced five extreme drought events during the period of 1971-2016, although temporal inconsistencies between the SPI and SPEI, particularly in 6- and 12-month timescales exist. Considering the SPEI, the results indicated a slight descending trend in the observed drought events; however, the SPI does not conform to the same pattern.
Keywords: Drought; SPI; SPEI; Trend; Ankara